Crop production diversity or market access?: Welfare outcomes among sorghum-growing households in rural Kenya and Uganda - Narmandakh, Davaatseren; Marenya, Paswel; Opie, Hellen; Bett, Charles (IAAE, 2024)
In market-constrained environments such as those found in dryland agroecologies, farm families face the decision to self-provision for diet diversity through crop diversification or to specialize in a few crop (non-agriculture) enterprises based on market exchange. However, the latter strategy is constrained by the usual market access problems prevalent in rural Africa (especially in dryland geolocations). This study contributes to the ongoing development discourse and research by examining the welfare effects of greater market access and participation compared to farm production diversity in rural Kenya and Uganda. Using crosssectional data from 2,398 households and three novel instrumental variables to isolate empirical correlates between market access and production diversity (as LHS variables) and diet diversity and food security, we find that both market participation and production diversity positively impact food security and welfare. One unit increase in farm production diversiy is associated with a 20.8% increase in the value of food consumed from farm. In contrast, in villages with stronger market links, farm diversity significantly affects the value of food purchases. A 10% increase in sorghum market participation is associated with a small increase in household diet diversity (2.02%), the value of food purchases only in villages where there are limited grain market opportunities. A 10% market participation of sorghum is though associated with a 15% increases farm expenditure in villages with weak market links. However, in villages with stronger market links, market participation negatively affects food purchases. Promoting market participation alone may heighten inequality if market infrastructure is weak.